The correlation of post-operative acute kidney injury and perioperative anaemia in patients undergoing cardiac surgery with cardiopulmonary bypass - Baranauskas, Tautvydas; Kaunienė, Agnė; Švagždienė, Milda; Širvinskas, Edmundas; Lenkutis, Tadas (Acta medica Lituanica, 2019)
Background and objective. Acute kidney injury (AKI) following cardiac surgery with cardiopulmonary bypass (CPB) is polyethiological clinical syndrome. During CPB haemodilution develops, which is useful in reducing the risk of thrombosis; however, haemodilutional anaemia decreases oxygen transfer and provokes tissue hypoxia, which can lead to acute organ damage. The aim of the study was to find out the impact of perioperative anaemia on AKI after cardiac surgery with CPB. Materials and methods. This prospective study included 58 adult patients undergoing elective cardiac surgery with CPB, without any preoperative chronic renal disease or any systemic autoimmune disease. Serum concentrations of NGAL had been tested before the surgery, 2 hours, 6 hours, and one day after the surgery. Perioperative anaemia was assessed according to the Ht value before the surgery, the Ht value during CPB, and immediately after the surgery. Results. The rate of haemodilutional anaemia is 77.59% in this study. The average of serum NGAL concentration before CPB was 63.95 ± 33.25 ng/mL and it was significantly lower than the average concentration 2 hours after the surgery, 6 hours after the surgery and one day after the surgery (respectively 148.51 ± 62.39, 119.44 ± 55, 128.70 ± 59.04 ng/mL, p < 0.05). AKI developed in 46.55% of the patients. A significant positive reasonable correlation between the development of perioperative anaemia and AKI was determined (r = 0.50, p < 0.05). Conclusions. Post-operative AKI after cardiac surgery with CPB has a moderate positive correlation with perioperative haemodilutional anaemia. A longer CPB time and aortic cross-clamping time were found to be the risk factors for the development of AKI.